Influence Of Merit System Implementation and Employment Relationson Employee Performance at The Bandung Advent Hospital - Ambarwati Ambarwati; Freddy J. Rumambi; Dwi Hernuningsih; Rudianto Rudianto; Marisi Pakpahan; Yopi J. Kameo (International Forum of Researchers and Lecturers, 2024)
The Merit System is an approach that emphasizes employee assessment based on abilities, achievements, qualifications and work results carried out fairly. Work relationships include interactions between employees with both colleagues and superiors. The Merit System will run well followed by a person's work relationship running harmoniously so that a person will have a commitment to work well. A person's performance is categorized as performing well in accordance with the targets/standards set by the company. This research aims to analyze the effect of implementing the merit system and employment relations on employee performance at Bandung Adventist Hospital. The research method used was quantitative research with descriptive analysis with 89 employee respondents. The results of this research show that the implementation of the merit system does not have a significant effect on employee performance, while work relationships have a significant effect on employee performance. The combined effect of the implementation of the merit system and work relations on employee performance has a significant effect of 18.2%. From this data it can be concluded that implementing a merit system in accordance with Law No. 5 of 2014 and working relationships that have good communication can improve employee performance.